Pengaruh Ulama Kharismatik di Padang Pariaman Dalam Perubahan Sosial Studi Terhadap Syekh H. Ali Imran Hasan (1926-2017) - Armaidi Armaidi (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Charismatic of a cleric is at least visible from the extent to which Muslims are able to make these scholars as role models and role models. The charismatic is even more apparent if the cleric establishes an Islamic boarding school or has a particular congregation. Like the charismatic cleric in Padang Pariaman Syekh H. Ali Imran Hasan (1926-2017) who pioneered and managed the Nurul Yaqin light-Islamic boarding school in Nagari Pakandangan, Padang Pariaman Regency, West Sumatra Province. The pesantren that he founded continues to grow and have branches in various regions in West Sumatra. In addition, this pesantren is proven to give birth to scholars who not only teach religious knowledge. Charismatic scholars also become agents of social change while being able to become a figure of community empowerment in the vicinity